The Impact of Continuous Cardiac Rehabilitation on the Psychological and Physiological Prognosis of Patients with Heart Failure—A Retrospective Study - Yan LH; Ge Y; Wang F; Zhu YL; Lu L (Therapeutics and Clinical Risk Management)
Li-Hua Yan,1 Yun Ge,1 Fei Wang,2 Yu-Ling Zhu,2 Li Lu1 1Department of Cardiovascular Internal Medicine, Nantong First Peoples’ Hospital, Nantong University Second Affiliated Hospital, Nantong, Jiangsu, 226014, People’s Republic of China; 2Department of cardiovascular Surgery, Nantong First Peoples’ Hospital, Nantong University Second Affiliated Hospital, Nantong, Jiangsu, 226014, People’s Republic of ChinaCorrespondence: Li Lu, Department of cardiovascular internal medicine, Nantong First Peoples’ Hospital, Nantong University Second Affiliated Hospital, No. 666 Shengli Road, Chongchuan District, Nantong, 226014, People’s Republic of China, Tel +8613515215905, Email drluli001@163.comObjective: This study aimed to assess the impact of continued cardiac rehabilitation on cardiac function, psychological well-being, and prognostic outcomes in patients diagnosed with heart failure and improved ejection fraction (HFimpEF).Methods: This study adopted a retrospective design, and a total of 150 patients with HFimpEF who experienced reduced ejection fraction after the first acute myocardial infarction were included. All patients underwent emergency percutaneous coronary intervention (PCI). Participants were categorized into a control group (n = 70) or an observation group (n = 80) based on their participation in ongoing cardiac rehabilitation. The follow-up period extended for one year. Comparative analyses were conducted to assess differences between the two groups in baseline characteristics, cardiac function, anxiety and depression scores, and the incidence of cardiovascular events.Results: No statistically significant differences were observed between the groups in terms of sex, age, past medical history, blood lipid levels, blood glucose levels, or renal function. Similarly, pre-treatment assessments of cardiac function, six-minute walk test results, Self-Rating Anxiety Scale (SAS) scores, Self-Rating Depression Scale (SDS) scores, or the incidence of cardiovascular events showed no significant differences. Compared to the control group, the observation group demonstrated significantly better cardiac function and six-minute walk test performance, along with significantly lower SAS and SDS scores. Furthermore, the incidence of heart failure and rehospitalization was significantly lower in the observation group than in the control group.Conclusion: Sustained cardiac rehabilitation in patients with HFimpEF was associated with significant improvements in cardiac function, enhanced six-minute walk test performance, reduced anxiety and depression levels, and a lower incidence of heart failure and rehospitalization. These findings highlight the key role of sustained cardiac rehabilitation in improving clinical outcomes for patients with HFimpEF.Keywords: cardiac function, cardiac rehabilitation training, heart failure with improved ejection fraction, mood, prognosis